The impact of micronutrient supplementation on the outcome of In Vitro Fertilization: A comprehensive systematic review of current studies - Abdullah, Muhammad Raoul Taufiq; Suryoadji, Kemal Akbar; Fakhri, Aldithya; Hestiantoro, Andon (Universitas Airlangga, 2025)
HIGHLIGHTS Potential benefits of vitamin D3 supplementation >20 ng/ml, along with myo-inositol, folic acid, and melatonin, on implantation rates. Subsequent studies revealed no substantial enhancement in pregnancy rates when specific supplements were used. Further research is needed to provide more definitive conclusions. ABSTRACT Objective: In vitro fertilization is the most common form of assisted reproductive and fertility technology. However, it is important to note the success rates of IVF generally decrease as a person gets older. Identifying modifiable factors affecting human fertility, including diet, is significant for clinical and community wellness. This systematic review investigates the role of micronutrients supplementation in fertility and its potential impact on in vitro fertilization (IVF) outcomes. Materials and Methods: A systematic search in multiple databases using specific keywords related to in vitro fertilization, micronutrient supplementation, and outcome measures. Results: Out of 1462 retrieved studies, 8 were included in the systematic review. These studies covered a range of micronutrients and their effects on different IVF outcomes. Findings indicated potential benefits of vitamin D3 supplementation. Vitamin D3 supplementation was associated with a significant improvement in implantation rates (p < 0.05) in two studies, while no significant effect was observed in clinical pregnancy rates in other micronutrients. The systematic review highlights the diverse effects of various micronutrient supplements on IVF outcomes. While some supplements showed potential benefits, others did not significantly improve pregnancy rates. Further research with larger cohorts is necessary to establish conclusive evidence. Keywords: micronutrient supplements, IVF outcomes, pregnancy rates. Conclusion: In conclusion, this systematic review sheds light on the impact of micronutrients on IVF outcomes. Some studies suggested potential benefits of vitamin D3 supplementation >20 ng/ml, further research is needed to provide more definitive conclusions. Understanding the function of micronutrients in fertility could have significant implications for IVF treatment and female infertility management.